2016
DOI: 10.1017/s0266467416000547
|View full text |Cite
|
Sign up to set email alerts
|

Plant communities and ecosystem processes in a succession-altitude matrix after shifting cultivation in the tropical montane forest zone of northern Borneo

Abstract: Abstract:Plant communities and ecosystem processes in seres at multiple altitudes in the tropical montane forest zone of northern Borneo were studied to understand the patterns and mechanisms of the secondary succession after shifting cultivation. A total of 25 stands (and additional three stands) were sampled with stand ages ranging from 2 to 55 y after slash and burn at altitudes between 900 and 1400 m asl. Plant species composition, above-ground biomass (AGB), chemical properties of soils, litter and foliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…The soil acidity, however, increases and nutrients decrease during the cultivation phase due to the utilization of organic matter by crops (Arunachalam, ). In contrast to our findings of an increase in nitrogen and phosphorus with age, there was no significant increase in these macronutrients with the stand age in a tropical montane forest in Borneo (Fujiki et al ., ). This was suggested to be a consequence of plants taking up nitrogen and phosphorus during succession.…”
Section: Discussionmentioning
confidence: 97%
“…The soil acidity, however, increases and nutrients decrease during the cultivation phase due to the utilization of organic matter by crops (Arunachalam, ). In contrast to our findings of an increase in nitrogen and phosphorus with age, there was no significant increase in these macronutrients with the stand age in a tropical montane forest in Borneo (Fujiki et al ., ). This was suggested to be a consequence of plants taking up nitrogen and phosphorus during succession.…”
Section: Discussionmentioning
confidence: 97%
“…One family slashes and burns patches of young-to old-growth forests, cultivates upland rice for the first year, and abandons the land for fallow [22]. In between the two parks, there is another local forest reserve (Tenompok Forest Reserve) with pristine vegetation, which is strictly protected from any subsistence use by local regulations.…”
Section: Study Site and Field Surveymentioning
confidence: 99%
“…To evaluate the spatiotemporal relationships between ecosystem services and farmlands, the integration of ecological understanding and remote-sensing data is crucial [21]. Fujiki et al [22] found that plant-species composition (richness) and above-ground biomass (a surrogate of carbon stock) demonstrated explicit temporal patterns after the abandonment of slash-and-burn cultivation in the same Bornean upland area where we conducted this study. In this case, the time elapsed after slash and burn is the most important determinant of species composition and biomass in the secondary-vegetation patches of this site.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations